2022
DOI: 10.1109/jstars.2022.3187722
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised Hyperspectral Denoising Based on Deep Image Prior and Least Favorable Distribution

Abstract: This paper considers the inverse problem under hyperspectral images (HSIs) denoising framework. Recently, it has been shown that deep learning is a promising approach to image denoising. However, deep learning to be effective usually needs a massive amount of training data. Moreover, in a practical scenario, HSIs may get contaminated by different kinds of noises such as Gaussian and/or sparse noise. Lately, it has been reported that the convolutional neural network (CNN), the core element used by deep image pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 63 publications
0
1
0
Order By: Relevance
“…Of course, some models can achieve this function in an unsupervised way, such as the GAN network, but the performance of these methods is limited and always significantly worse than the performance of supervised methods. How to further enhance, especially by adding prior physical knowledge into training, the performance of unsupervised solutions is a burning problem [64,227].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of course, some models can achieve this function in an unsupervised way, such as the GAN network, but the performance of these methods is limited and always significantly worse than the performance of supervised methods. How to further enhance, especially by adding prior physical knowledge into training, the performance of unsupervised solutions is a burning problem [64,227].…”
Section: Discussionmentioning
confidence: 99%
“…To handle this issue, in 2022, Ref. [227] proposed a user-friendly unsupervised hyperspectral images denoising solution under a deep image prior framework. Extensive experimental results demonstrate that the method can preserve image edges and remove different noises, including mixed types (e.g., Gaussian noise, sparse noise).…”
Section: Rs Casementioning
confidence: 99%
See 1 more Smart Citation
“…In this study, Imamura et al, proposed a fully CNN network a trained it by manually adding noise the noisy HSI, while the model's objective was to generate the original image from the noisy one. In another study for HSI denoising, Faghih et al, (2022) proposed an unsupervised method using a deep image prior (DIP) UNet architecture [135]. They showed that DIP trained with Huber loss function can generate denoised HSI without needing training data.…”
Section: Data Preprocessing (Denoising Fusion Super-resolution)mentioning
confidence: 99%
“…Criminisi et al propose a texture synthesis method [11] ,which is mainly implemented by repeatedly computing the priority of the restored region [12] , propagating the texture information and updating the confidence level, but with the consequent repetition of steps, the confidence level decreases, leading to errors in the filling order.…”
Section: Patch-based Approachmentioning
confidence: 99%